Laboratory Measurement Instrument for Testing Broadband Image Sensor - Šusta, Michal; Zahradnik, Pavel; Šimák, Boris (International Society for Science and Engineering, o.s., 2019)
In the development of a unique broadband camera based on carbon nanotubes, a proprietarytesting system was designed. This system is suitable for testing, measuring and calibrationof parameters of functional blocks of the camera in laboratory conditions including its essential partwhich is the broadband MEMS microbolo-meter based array sensor. This article deals with the methodologyand the way of solving the electrical and mechanical aspects of the construction of themeasuring instrument. It also explains the principle of the block structure of the computing part forthe data processing and its links to the structure of the control circuitry with the application of adigital signal processor.

In the development of a unique broadband camera based on carbon nanotubes, a proprietarytesting system was designed. This system is suitable for testing, measuring and calibrationof parameters of functional blocks of the camera in laboratory conditions including its essential partwhich is the broadband MEMS microbolo-meter based array sensor. This article deals with the methodologyand the way of solving the electrical and mechanical aspects of the construction of themeasuring instrument. It also explains the principle of the block structure of the computing part forthe data processing and its links to the structure of the control circuitry with the application of adigital signal processor.